Assessment of Maximum Velocity: A Case Study of Pogon Szczecin Football Players in Polish Ekstraklasa - Łukasz Rosiński; Anna Rzepiela-Podlecka; Rafał Buryta (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The aim of this study was to assess the maximum velocity achieved by professional soccer players. The study involved 20 professional football players. The analysis of the achieved velocities during the season was based on individual maximum velocity values obtained in a preseason period test using the GPS monitoring device Catapult Vector S7. The study covered 20 match units and 77 training units. A velocity equal to or greater than 100% of the maximum velocity was achieved 24 times - 21 times (accounting for 88%) during a competitive match (MD 0), 1 time (accounting for 4%) two days before (MD-2), and two times (accounting for 8%) three days before (MD-3). A velocity in the range of 90-99% of the maximum velocity was achieved 207 times. The results confirm that football players can achieve values equal to or greater than 100% of their maximum velocities; however, this occurrence is rare. Due to the low probability of high maximum velocity values during a training microcycle, it is recommended to incorporate specific training methods that allow for achieving high maximum velocities to reduce the risk of hamstring muscle injuries among players, especially among reserve players (who rarely participate in competitive matches).